Les trajectoires dans le temps: réflexion sur le concept de « régime d’historicité » - Maxime Raymond-Dufour (Conserveries Mémorielles)
This paper offers a critical take on the conceptual framework of "régime d'historicité" as understood by François Hartog in his book Régimes d’historicité : Présentisme et expérience du temps. Although heuristically useful, the "régime d'historicité" can generate conceptual problems when one tries to qualify with precision the experience of temporality in human societies. Once reified in historical reality, the globalizing interpretation offered by Hartog's conceptual framework tends to identify a dominant experience of temporality in a given "régime", therefore considering other experiences as non-structuring or simply peripheral. I rather consider that theses alternative experiences can contribute to a "régime d'historicité" even if they don't converge with the dominant "orientation" of time. Thus, I propose to examine 1) the multiplicity of the "régime d'historicité"'s experiences and 2) the relation between the historical object and the "orientation" of time, both being closely tied to each other.